Visibility vis-à-vis effectiveness of aid: looking for the third way - Frank Vollmer (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Official development assistance (ODA) is constantly under pressure to justify its raison d'être. Hence, calls for more visibility are frequently raised at the headquarters level. At the same time, reports that such calls for more visibility can undermine efforts towards achieving aid effectiveness continue to appear, particularly from aid practitioners at the field level. With these different views in mind, it is time to think more intensively about visibility and its implications for the aid effectiveness agenda. First, a conceptual discussion should be started. Next, it is necessary to better understand the relationship of the two calls, one for “more visibility” and one for “more effectiveness”. Can ODA be more visible and remain effective at the same time? Or does achieving one demand sacrifice the other? Starting with the claim that visibility could be a valuable asset for promoting the aid effectiveness agenda, there are three main arguments to support this point. First, the implementation of the principles and commitments of the Paris Declaration (PD) and Accra Agenda for Action (AAA) – confirmed in the Busan Partnership for Effective Development Co-operation – implicitly demands greater visibility of the agenda as such in the political and public domains. In particular, the PD requires “continued highlevel political support, peer pressure and coordinated actions” (par. 8). Greater visibility of the agenda is therefore necessary to ensure its continued relevance. Second, visibility in the form of information exchange is a precondition for development actors to coordinate and act jointly. Third, agents have to be visible at some stage of the aid delivery chain for legitimising actions vis-à-vis their respective principals. But the desire for visibility can also be seen as a potential risk for the implementation of the aid effectiveness agenda. Visibility can have adverse effects if the yearning for visibility at the agency level outweighs approaching aid delivery, according to the PD. Such “declaration-style” aid is defined as being “clearly aligned to country priorities and system, coordinated by the country and/or provided through harmonised or multi-donor arrangements, untied, predictable and transparent” (Wood et al. 2011, xi). Actions should be geared towards the achievement of substantial and sustainable development outcomes. “Declaration-style” aid is undermined if the desire for visibility incentivises a “free for all” situation, a relapse into the turmoil of “competitive, uncoordinated and donor-driven activities” (ibid., xv) that the PD set out to overcome by demanding joint action. Looking at the bigger picture, is it possible to have more visibility and more effectiveness simultaneously? A clear “definitely maybe”. To begin, it is not a win-win situation, considering that development actors tend to think of “agency” visibility and “group” effectiveness. Thus, might this be a case of “impossible geometrics”? Only if agents insist on input and activities visibility, which is the kind of visibility that hinders joint efforts the most. Might there be a third way? I will argue yes – in the form of an acceptable trade-off. If agents (a) present their efforts as contributions to jointly achieved development outcomes, and if agents (b) are willing to be creative, and to enrich visibility with meaningful communication strategies that explain eventual losses of individual visibility for the sake of functioning joint efforts, then losing a certain kind of visibility – input visibility – might be an acceptable tradeoff for achieving the higher goal: aid effectiveness.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Wirksamkeit und Evaluierung; Aufstrebende Mächte